Resource reclaiming in a uni-processor real time system - Soong, Si Young. (2008)
This dissertation examines a fundamental problem in the theory of real-time scheduling. Real-time scheduling of a set of aperiodic task with soft deadlines on a uni-processor without preemption and without inserted idle time was investigated. Idle gap as a results of the difference between estimated computation time and actual computation time was reclaimed to run the scheduler. Introduction of this scheduling approach will increase the CPU utilization and maximizing the deadline hit ratio.